(untitled) (Paliativní medicína, 2025)
The aim of this article is to analyse the psychological burden of social workers in palliative care and identify sources of support that contribute to maintaining their mental health. Theoretical part of the article deals with the specifics of social work in the context of palliative care, particularly in the hospital setting. For the research part, the following method was chosen qualitative research strategy using semi-structured interviews. Research focused on health and social workers in hospital palliative care.